2011
DOI: 10.1024/0036-7281/a000223
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dog erythrocyte antigen 1.1 in dogs in Switzerland evaluated with the gel column technique

Abstract: Canine blood typing has become an established and essential laboratory test due to the rising demand for safe and efficient blood transfusions. The most immunogenic and clinically important blood type is DEA 1.1. Little is known about DEA 1.1 frequencies or special characteristics among different canine breeds. 304 dogs were tested for DEA 1.1. DEA 1.1-typing was performed using a commercial gel column technique (ID-Gel Test Canine DEA 1.1, DiaMed, Cressier, Switzerland). Fifty-three percent of all tested dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
3
11
1
Order By: Relevance
“…These results are comparable to those found in other previous investigations: 78.0–100% in Rottweiler, 77.0–95.0% in Golden Retriever, and 71.0–100% in Dachshund [24, 28, 29, 36, 37]. It is important to know the frequency of DEA 1 positive blood type in the Rottweiler and Golden Retriever as they could be enrolled as blood donors, because their weight is in the range established for donations and they are generally docile dogs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are comparable to those found in other previous investigations: 78.0–100% in Rottweiler, 77.0–95.0% in Golden Retriever, and 71.0–100% in Dachshund [24, 28, 29, 36, 37]. It is important to know the frequency of DEA 1 positive blood type in the Rottweiler and Golden Retriever as they could be enrolled as blood donors, because their weight is in the range established for donations and they are generally docile dogs.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the Labrador Retriever breed showed a high prevalence for DEA 1 positive type (65.3%) as reported previously in studies carried out in Switzerland, South Africa, and Italy [24, 29, 37]. Nevertheless, in the published study from Portugal, Labrador Retrievers showed a higher prevalence for DEA 1 negative type (55.0%), although those results could be related to the low number of dogs (number 29) tested in comparison to our data (number 478) [28].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Blood typing methods have evolved from tube and card tests to immunochromatographic strip, cartridge, and flow cytometry assays, but additional typing kits for other blood types would be desirable (1,(21)(22)(23)(24). Several limited surveys have been performed for DEA 1, and a few have assessed other blood types in North America and Europe (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), but there have been no comprehensive surveys carried out on a canine population typing for many blood groups.…”
Section: Introductionmentioning
confidence: 99%